Targeting Interleukin 13 for the Treatment of Atopic Dermatitis - Yuliya Lytvyn; Melinda Gooderham (MDPI AG, 2023)
Atopic dermatitis (AD) is a common chronic inflammatory skin condition that has a significant impact on a patient's quality of life and requires ongoing management. Conventional topical and systemic therapies do not target specific components of AD pathogenesis and, therefore, have limited efficacy and may be associated with long-term toxicity. Thus, AD management is challenging, with a significant proportion of patients not achieving clear skin or a reduction in pruritus. There remains a large unmet need for effective therapeutic strategies with favorable safety profiles that can be used long-term in patients with refractory AD. The emergence of targeted biological and small molecule therapies has effectively broadened available treatment options for moderate-to-severe AD. Most recently, interleukin 13 (IL-13) inhibitors were shown to be efficacious and well-tolerated, with tralokinumab already approved for use in this patient population. It is important for dermatologists to be aware of the evidence behind this emerging class of biologic agents to guide treatment choices and improve outcomes in patients with AD. The main objective of this paper is to review the current literature regarding the efficacy and safety of current and emerging anti-IL-13 monoclonal antibodies, including tralokinumab, lebrikizumab, cendakimab, and eblasakimab, for the treatment of moderate-to-severe AD.